Effect of weed management on performance of sesame (Sesamum indicum l.) under varying levels of nitrogen - Dhaka, M.S.; Yadav, S.S.; Shivran, A.C.; Choudhary, G.L.; Prajapat, K. (Annals of Agricultural Research, 2014)
Short note